Bioaccumulation of Carbofuran and Endosulfan in the African Catfish Clarias gariepinus - Mohamed Abu Zeid, Isam Eldin; Syed, Mohd Arif; Ramli, Johari; Arshad, Juzu Hayati; Omar, Ismail; Shamaan, Nor Aripin (Universiti Putra Malaysia Press, 2005)
The African catfish Clarias gariepjnus was exposed to a sublethal dose of 14ecarbofuran and 14G-endosulfan. Mter 1, 6, 12, 24, 72 and 144 h, the fish were removed and insecticide residues determined in the liver, intestines, gills, brain and skeletal muscles. Highest levels of residues, per g dry weight of tissues, was found in the liver (354 ± 6 Jlg carbofuran and 1409 ± 43 ng endosulfan after 24 h) followed by the intestines (239 ± 1 Jlg carbofuran and 1147 ± 21 ng endosulfan after 72 h), the gills (108 ± 2 Jlg carbofuran and 817 ± 19 ng endosulfan after 24 h), brain (57 ± 2 Jlg carbofuran after 24 h, 555 ± 19 ng endosulfan after 72 h) and skeletal muscle (25 ± 1 Jlg carbofuran after 144 h and 364 ± 13 ng endosulfan after 6 h). The residue levels were rapidly accumulated in the tissues. Based on the levels of pesticide residues after 1 h, all the tissues recorded very high levels of residues after 6 h. After reaching maximum levels in the tissues at various times of exposure, the residue levels in all the tissues began to decrease over time.